Factors associated with stage of behavior change and willingness to quit smoking among people living with HIV In Taiwan - Linlin Lindayani; Yiin Lai; Wen-Chien Ko; Jung-Der Wang; Nai-Ying Ko (Jurnal Keperawatan Padjadjaran, 2025)
Background: The prevalence of smoking among people living with HIV is double than general population. There is no specific guideline for smoking cessation in this population thus many of HIV-smoker receive unproven treatment that led to low adherence and high relapse. Objectives: The aim of this study was to identify the stage of behavior change and willingness to quit smoking, and to determine their associated factors among people living with HIV. Methods: A cross-sectional design was conducted at an HIV/AIDS hospital in southern Taiwan. of 423 people living with HIV, the mean age was 37.43 (SD=10.99) years and 97.9% were male. About 33.9% were a current smoker, 22.9% were in pre-contemplation stage, and 33.3% willing to quit smoking. Age, education, CD4 cell counts, viral load, having diabetic and hepatitis B, and exposure to smoking cessation information were associated with stage of behavior change. Smoking 2-3 times a month (aOR=9.33, 95%CI= 1.45-60.2) and having heard about smoking cessation were significant predictors for willingness to quit smoking (aOR= 3.67, 95 CI= 3.67-9.06). Conclusion: Our findings suggest to design an intervention according to HIV-smoker stage of behavior change for successful smoking cessation. Additionally, it is important to address patients’ clinical conditions including smoking frequency and exposure to information related to smoking cessation.